Whole body‐diffusion weighted imaging for the assessment of treatment response in hairy cell leukaemia: A positive first step. Issue 2 (2nd February 2021) - Algudkar, Ashwin; El‐Sharkawi, Dima; Cross, Matthew; Tunariu, Nina; Attygalle, Ayoma D; Sharma, Bhupinder
Abstract: We present the case of a patient diagnosed with hairy cell leukaemia (HCL) who subsequently developed biopsy confirmed bone lesions and underwent multiple lines of therapy. The reported incidence of bone lesions in HCL is 3%, and bony involvement can be associated with high tumour burden and aggressive disease. The commonly lytic bone lesions in HCL are difficult to accurately assess for response. Whole body diffusion weighted imaging (WB‐DWI) has been used clinically in multiple myeloma; we postulate clinical utility in HCL, where hypercellularity also applies. In our case, WB‐DWI appears to discriminate sites of active disease from bone response. We present the salient radiological and pathological images. To our knowledge, this is the first description of WB‐DWI in HCL; we support research of WB‐DWI in the staging, prognostication and response assessment of HCL.